Entanglement, uncertainty and dispersion: a simple experimental demonstration of non-classical correlations. (14th February 2017) - Lerch, S; Guerreiro, T; Sanguinetti, B; Sekatski, P; Gisin, N; Stefanov, A
Abstract: We perform an experiment to verify the presence of entanglement in photon pairs. By sending down-converted light through dispersive media with opposite group velocity dispersion coefficients, we overcome the minimum broadening of temporal correlation for classical light. Entanglement is proved via an inequality derived directly from Heisenberg's uncertainty principle. We present a criterion to select a suitable down-conversion source. Moreover, we introduce a new method to analyze the temporal correlations between the entangled photons.